TREATMENT RECOMMENDATION IN VIETNAMESE MEDICAL CONSULTATIONS - Nguyen, Huong Thi Linh; Austin, Gavin; Chau, Dung Duc (PEOPLE: International Journal of Social Sciences, 2018)
This study investigated the doctor’s recommendation of treatment to their adult patients in primary-care visits in the Vietnamese context. Data was gathered from 55 audio-recorded consultations at two public hospitals, and examined from a conversation-analytic perspective. We demonstrate that the participating doctors used two main approaches to treatment recommendation with their patients: general and detailed. In the latter case, the doctor recommended a treatment regime, sought the patient’s agreement, or offered choices regarding aspects of the treatment. Our overall contention is that, in the Vietnamese public hospital system, the doctor’s organisation of talk in the course of recommending treatment tends to be shaped by the institutional and cultural context in which it occurs, regardless of which type of treatment approach is being used.